Evolutionary adaptation and mitogenomic diversity of spiders associated with Nepenthes smilesii Pitcher Plants in Thailand - Fah Lertkulvanich; Natapot Warrit; Mingkwan Nipitwattanaphon (PLoS ONE, 2026)
Symbiosis is a close physical interaction between organisms, shaped by species-specific traits and environmental factors. The tropical pitcher plant, Nepenthes , exemplifies a predator-prey relationship; however, certain small invertebrates benefit from the pitcher plant without being subjected to predation. For example, spiders from the Thomisidae family inhabit the digestive fluid of the plant without being digested, preying on the organisms captured by the plant. These spiders offer a valuable model for investigating evolution driven by specialized niches compared to free-living relatives. This study characterized the mitogenomes of four spiders residing within the pitchers of Nepenthes smilesii in the Phu Kradueng National Park, Thailand: Thomisus sp., Henriksenia sp., Epidius sp. (Thomisidae), and Pseudopoda sp. (Sparassidae). The mitochondrial genomes measured 14,731 bp, 15,888 bp, 14,289 bp, and 14,533 bp, respectively, each consisting of 37 genes, characteristic of metazoan mitogenomes. Higher rates of nonsynonymous substitution were observed in the ND2, ND5, and ND6, genes of these pitcher-associated spiders compared to free-living species of the same families, indicating the evolutionary drivers linked to the pitcher plant environment. Distinct gene rearrangements were identified in the three Thomisids, including the duplication of two control region-like sequences in Henriksenia sp., while Pseudopoda sp. exhibited a typical mitogenome structure. The phylogenetic tree constructed using all 13 protein-coding genes provided significantly stronger bootstrap support compared to the tree based on 600 bp COI sequences. It also revealed that Thomisus sp. and Henriksenia sp. are clustered within a single monophyletic clade, while Epidius sp. was more diverse and formed a paraphyletic group relative to the rest of Thomisidae family. These results provide essential data for systematic studies and illuminate the co-evolutionary genomic signatures of pitcher plant-spider associations.